Everything Blended: Engaging Combinations, Appropriations, Bricolage, and Syncretisms in Our Teaching and Research - McCloud, Sean (Implicit religion, 2018)
In this essay, I open a discussion on how the blending and combining of cultural elements are understood and engaged in our classrooms and research. Specifically, I do two things. First, I illustrate that combining and blending practices, while perhaps more visible in the contemporary period, are a constant in American religious history. Second, I provide a case study of Third Wave Spiritual Warfare that heeds the anthropologist Charles Stewart's suggestion that one useful way to approach syncretism (and its synonyms) is by examining the discourses and debates that individuals and groups have over what activities and ideas are viewed as such. Overall, I argue that we need to develop a method for both teaching and examining the appropriative bricolage that makes up religious practices.